Etidronate from Medicine to Endodontics: effects of different irrigation regimes on root dentin roughness. - TARTARI, Talita (2014)
An increase in dentin roughness, associated with surface composition, contributes to bacterial adherence in recontaminations. Surface roughness is also important for micromechanical interlocking of dental materials to dentin, and understanding the characteristics of the surface is essential to obtain the adhesion of root canal sealers that have different physico-chemical characteristics.